2008
DOI: 10.1097/pap.0b013e3181836a03
|View full text |Cite
|
Sign up to set email alerts
|

Gray Zones in Brain Tumor Classification

Abstract: The World Health Organization recently updated its classification of central nervous system tumors, adding 8 entities, as well as defining new variants and morphologic patterns of existing entities. Despite the continued refinement of brain tumor histologic classification and grading, there remain some diagnostic "gray zones" that challenge general surgical pathologists and neuropathologists alike. These include the presence of oligodendroglial features in (mixed) oligoastrocytomas and glioblastomas (GBMs), GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 64 publications
1
27
0
2
Order By: Relevance
“…However, several studies report that histologic diagnosis of glioma established after stereotactic biopsy, from a single point in the tumor, is associated with a substantial risk of inaccuracy. 24 Moreover, a biopsy cannot always be obtained: some tumors are not accessible to the surgeon and no repeated biopsies of a brain tumor are performed during the therapeutic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies report that histologic diagnosis of glioma established after stereotactic biopsy, from a single point in the tumor, is associated with a substantial risk of inaccuracy. 24 Moreover, a biopsy cannot always be obtained: some tumors are not accessible to the surgeon and no repeated biopsies of a brain tumor are performed during the therapeutic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…GFAP is considered to be a general marker for astrocytes in the central nervous system (20). The accurate diagnosis of brain invasion is therefore critical and, in borderline cases, an immunohistochemical stain for GFAP aids in the delineation of entrapped glial elements within the substance of a brain-invasive meningioma (21).…”
Section: Case Reportmentioning
confidence: 99%
“…In general, the pathological nature of meningioma determines its association with the brain parenchyma, which is that benign meningioma is usually compressive to the brain parenchyma due to its expansive growth, and malignant meningioma is invasive into the neighboring brain parenchyma due to its intrusive growth (5,6). However, clinical observations have indicated that there is a sub-group of benign meningioma displaying a malignant growth pattern, that is, invasion into the neighboring brain tissue (7)(8)(9)(10)(11). This sub-type of meningioma is usually unnoticed prior to surgical resection by the neurosurgeon, which can often result in damage of the neighboring brain tissue.…”
Section: Introductionmentioning
confidence: 96%